Facilitative Glucose Transporter Type 1 Is Differentially Regulated by Progesterone and Estrogen in Murine and Human Endometrial Stromal Cells - Frolova, Antonina (The Endocrine Society, 2009)
Embryo implantation is a highly synchronized event between an activated blastocyst and a receptive endometrium. The success of this process relies on the dynamic interplay of estrogen (E(2)) and progesterone (P(4)), however, the details of this interaction are not entirely clear. Recent data implicate E(2) and P(4) in the regulation of glucose utilization by affecting facilitative glucose transporter (GLUT) expression. In this study we examine GLUT1 expression in murine and human endometrial stromal cells (ESCs) using a primary culture system. We show that expression of GLUT1 is increased during ESC decidualization in vitro. P(4) up-regulates, whereas E(2) down-regulates, GLUT1 expression. In addition, P(4) increases and E(2) decreases glucose uptake in ESCs, suggesting that GLUT1 may be a major player in glucose utilization in these cells. Moreover, GLUT1 expression is increased in human ESCs when decidualized in vitro with P(4) and dibutyryl cAMP, suggesting a similar role for P(4) in human endometrium. In conclusion, an imbalance between P(4) and E(2) seen in patients with polycystic ovary syndrome, luteal phase defect, and recurrent pregnancy loss may have a critical impact on glucose utilization in the endometrial stroma, and, thus, may be responsible for endometrial dysfunction and failure of embryo implantation in these patient populations.